Poverty Depiction in Egyptian Films Across the Decades: A Comparative Content Analysis of Framing Poor Characters in Egyptian Cinema Between 1955 and 2010 - Daly, Moustafa Abdelfadil (AUC Knowledge Fountain, 2023)
This research examines the framing of poverty in Egyptian film productions during a 55-year period from 1955 to 2010. It uses a qualitative analysis to identify and analyze main characters depicted to be poor in films produced under three political eras; Gamal Abdel-Nasser, Anwar El Sadat, and Hosny Mubarak. It analyzes the frequency of featuring poor characters and whether the depiction of poor people was favorable or unfavorable based on three constructs; accountability of poverty, heroism, and honesty. Out of 41 main characters studied, 22 were found to be poor, with Nasser's era witnessing the highest representation of poverty. Most characters were also found to be accountable for their own poverty, indicating an overall tendency to depict poverty as the responsibility of the poor, not due to structural, social and economic inequalities caused by public policies, except under Nasser’s regime. Eight characters were depicted as heroes, while six were depicted as villains, possibly indicating a tendency to glorify poverty and promote the heroic poor image as opposed to the troublesome, evil poor. In contrast, 13 characters were depicted to be dishonest, while six characters were depicted to be honest. The study concludes that poverty was overrepresented under Nasser’s regime, indicating higher prominence for poorer character during the socialist era than the following neo-liberal eras under Mubarak and Sadat. It also found that unlike other regimes, under Nasser, the poor were found to be unaccountable for their poverty, and so worthy of state support. Films during that era also glorified poor characters as heroes and villainized richer characters.